Power system fault diagnosis using artificial intelligent - Abdullah Asuhaimi Mohd. Zin, 1952- 602136; Alias Mohd. Yusof, 1951-2014 311071; Alireza Tavakoli Ghainani 384099; Student Conference on Research and Development (SCOReD 2001) (2001 : Kuala Lumpur) 475181 (Skudai : Universiti Teknologi Malaysia, 2001)
15